2022
DOI: 10.3390/met12091470
|View full text |Cite
|
Sign up to set email alerts
|

The Use of CFRP for Structural Reinforcement—Literature Review

Abstract: Carbon fiber reinforced polymer (CFRP) composites are increasingly being used to strengthen structures and to retrofit existing structures. CFRP composites are used in various industries: construction, automotive, and many others. This literature review has shown that CFRP composites find numerous practical applications. Improving structures by reinforcing them with CFRP composite is an innovative approach in design. This review aims to explore the current state of the art in the types of structures that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…It is worth noting that, compared with the short beam method, the double beam method has a pure shear stress point, which alleviates the influence of bending stress on the shear strength between layers to a certain extent [71,72]. At the same time, considering the application of double-beam shear method to resin-based composites, it has some specificity compared with the traditional interlayer shear performance test, and is gradually widely used in the shear performance test of FMLs [73][74][75].…”
Section: Layer Plate Shear Failure and Index Evaluationmentioning
confidence: 99%
“…It is worth noting that, compared with the short beam method, the double beam method has a pure shear stress point, which alleviates the influence of bending stress on the shear strength between layers to a certain extent [71,72]. At the same time, considering the application of double-beam shear method to resin-based composites, it has some specificity compared with the traditional interlayer shear performance test, and is gradually widely used in the shear performance test of FMLs [73][74][75].…”
Section: Layer Plate Shear Failure and Index Evaluationmentioning
confidence: 99%
“…To use CFRP as a reinforcement material, it is necessary to be mindful of certain weaknesses. The primary weaknesses of CFRP include degradation at elevated temperatures, high cost, low ductility, and low shear strength [21]. The degradation of CFRP due to the low thermal decomposition temperature (approximately 250-350 o C) of the polymer matrix at elevated temperatures has drawn significant attention [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review shows that similar review papers published, with a similar topic, usually focus on one of the following research areas: manufacturing properties and applications of the carbon fibres and their composites [ 31 , 32 , 33 , 34 ]; properties and applications of aramid fibres and their composites including Kevlar fibres [ 12 , 35 ]; mechanical properties of hybrid composites [ 36 ]; strengthening of timber structural members with carbon- or glass-reinforced polymers [ 37 , 38 ]; strengthening of concrete structures with fibre-reinforced polymer composites [ 39 , 40 , 41 ]. Considering the papers published in the literature in recent years, addressing the applications of composite materials for the strengthening of different structural elements in building engineering (concrete and wooden beams, ballistic protection panels), it can be observed that most of the research which has focused on such applications use carbon fibres or Kevlar fibres or Kevlar–carbon hybrid fabrics.…”
Section: Introductionmentioning
confidence: 99%